Pemberdayaan Masyarakat melalui Program Desa Berdaya: Pelajaran dari Desa Bligo - Eny Boedi Orbawati; Fadlurrahman Fadlurrahman; Sujatmiko Sujatmiko; Ari Mukti (Society, 2024)
Desa Berdaya (Empowered Village) is an acceleration initiative in rural areas utilizing an integrated approach encompassing capacity building, economy, health, education, environment, and disaster preparedness. Its primary aim is to foster and develop local institutions to address community issues. This study seeks to portray the success of community empowerment through the Desa Berdaya program in Bligo Village, initiated by the private organization Rumah Zakat, by analyzing the 5P empowerment strategies: enabling, strengthening, protecting, supporting, and maintaining. A qualitative method with a case study approach was employed. Data collection was conducted using in-depth interviews, focus group discussions, observations, and documentation. Informants were selected purposively, including Bligo Village Government officials, Rumah Zakat facilitators, women’s farming groups, the Bligo Beriman waste bank, entrepreneurs, and local community members, totaling ten informants. The findings reveal that the implementation of the Desa Berdaya program in Bligo Village does not follow specific criteria but is based on program facilitators’ recommendations, often prioritizing their home villages. Based on the 5P empowerment strategy, the enabling stage involved dialogues with the village head, community leaders, and other key members deemed capable of implementing the Desa Berdaya program. During the strengthening stage, formal groups were formed, and collaborations with various internal and external parties were initiated. The protection stage was realized by issuing official decrees for the established groups, along with financial support from Rumah Zakat, Bligo Village Government, and the Magelang Regency Agricultural Office. The supporting stage was conducted through facilitation and guidance provided by program facilitators to the community. Finally, the maintenance stage was carried out by fostering a conducive atmosphere within the empowerment groups. The Desa Berdaya program positively impacts Bligo Village, particularly in social, health, environmental, and economic aspects. The reactivation of community groups and the establishment of a waste bank, which remains well-managed, are among the significant outcomes. The people of Bligo Village have become increasingly critical in addressing social and economic issues in their community due to the continuous empowerment process, which persists to this day.